2018
DOI: 10.1089/omi.2018.0027
|View full text |Cite
|
Sign up to set email alerts
|

Sarcoidosis Related Novel Candidate Genes Identified by Multi-Omics Integrative Analyses

Abstract: Sarcoidosis is a multifactorial systemic disease characterized by granulomatous inflammation and greatly impacting on global public health. The etiology and mechanisms of sarcoidosis are not fully understood. Recent high-throughput biological research has generated vast amounts of multi-omics big data on sarcoidosis, but their significance remains to be determined. We sought to identify novel candidate regions, and genes consistently altered in heterogeneous omics studies so as to reveal the underlying molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 65 publications
0
3
1
Order By: Relevance
“…Hočevar et al published recently a statistical analysis of genome-wide association study (GWAS). GWAS signals could be found increased in the region of NELF-E, SKIV2L, and STK19 genes [28]. In our study, we found only for NELF-E but not for SKIV2L or STK19 autoantibodies in sarcoid patients.…”
Section: Discussioncontrasting
confidence: 42%
“…Hočevar et al published recently a statistical analysis of genome-wide association study (GWAS). GWAS signals could be found increased in the region of NELF-E, SKIV2L, and STK19 genes [28]. In our study, we found only for NELF-E but not for SKIV2L or STK19 autoantibodies in sarcoid patients.…”
Section: Discussioncontrasting
confidence: 42%
“…Integration of different omics data presents comprehensive overviews of pathological molecular pathways that can be targeted for the development and application of precision medicine [200]. Multi-omics integrative analysis generates vast amounts of big data from sarcoidosis samples including genomic, transcriptomics, proteomic, and phenomic studies, all of which have been used to describe novel candidate regions and genes, altered in sarcoidosis [201]. These new data analysis methods are bridging the gap between conventional therapies and advanced care and are bound to open new therapeutic paradigms for this complex disease.…”
mentioning
confidence: 99%
“…One of those is located in a TPR domain ( Andreoletti et al, 2017 ). Variation in the cochaperones encoded by PTGES3L and FKBPL has also been potentially linked to various inflammatory disease ( Hocevar et al, 2018 ; Bianchi et al, 2021 ), but more analysis is required. Single-nucleotide variants in the HSP90AB1 and HSP90B1 genes have been proposed to modulate chronic obstructive pulmonary disease ( Ambrocio-Ortiz et al, 2021 ), and Hsp90 is known to regulate inflammatory processes ( Nizami et al, 2021 ).…”
Section: Link Between Cochaperones and Inflammatory Diseasementioning
confidence: 99%